2012
DOI: 10.1177/0956797611427168
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Children’s Arithmetic Performance Are Accounted for by Gender Differences in Language Abilities

Abstract: Studies have shown that female children, on average, consistently outperform male children in arithmetic. In the research reported here, 1,556 pupils (8 to 11 years of age) from urban and rural regions in the greater Beijing area completed 10 cognitive tasks. Results showed that girls outperformed boys in arithmetic tasks (i.e., simple subtraction, complex multiplication), as well as in numerosity-comparison, number-comparison, number-series-completion, choice reaction time, and word-rhyming tasks. Boys outper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 32 publications
5
94
4
1
Order By: Relevance
“…Nevertheless, a specific and small advantage is reported for boys for mathematical reasoning, perhaps reflecting higher aptitude with logical and set theoretical concepts (39). Conversely, an advantage specific to arithmetic is reported for girls, which seems to be attributable to the girls' higher verbal skills that are implicated in arithmetical processing (40).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, a specific and small advantage is reported for boys for mathematical reasoning, perhaps reflecting higher aptitude with logical and set theoretical concepts (39). Conversely, an advantage specific to arithmetic is reported for girls, which seems to be attributable to the girls' higher verbal skills that are implicated in arithmetical processing (40).…”
Section: Discussionmentioning
confidence: 88%
“…Girls in our sample may have benefitted from an overall advantage in language skills as well as in arithmetic and counting, whereas boys may have benefitted from an advantage with set theoretical concepts, with the latter being more critical for the specific task than the former. We should note that our analyses for gender effects were exploratory and that future studies should take into account several potentially confounding factors (40).…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al 18 assessed children in rural and urban areas of Great Beijing and found better performance of girls in the tasks of subtraction, complex multiplication, numeric comparison, and completing numerical series. The authors attributed these results to better language processing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, since we had more girls in the normally developing group (N = 11) than in the dyslexia group (N = 3) (p = 0.007), and that there were gender differences in the children's arithmetic performance (Wei et al, 2012), we reran all analyses co-varying with gender difference, and the pattern of results remained (please also see Table s1, Figure s1 of further analyses for this issue).…”
Section: Relationship Between Performances In Linguistic Measures Andmentioning
confidence: 95%